Employing Decorative Composition Between Originality and Contemporary in Furniture Designs - Mohammed Hassan Al-Hilo; Lilian Ali Ajaj (Journal of Techniques)
The decorative composition represents one of the most important aspects of heritage as the cultural value that affects one way or another on the successive generations. Many furniture designs that bear contemporary formal values have emerged, at a time when the issue of contemporary and its relationship to originality is one of the important issues that occupy the Arab community. The idea of the designer, and hence the research problem arose with the following question: How is the decorative composition employed between originality and contemporary in furniture designs? while the goal of the research is embodied in revealing the mechanism of employing decorative composition between originality and contemporary in furniture designs. As for the limits of the research, it was objectively determined by studying the employment of decorative formations between authenticity and contemporary, while ensuring its spatial and temporal limits in what Pinterest offers for the year 2021. The theoretical framework of the research consists of two sections, the first dealt with the concept of decorative composition, and the second dealt with the concepts of originality and contemporary. For fidelity and stability. The analysis process resulted in a number of results, the most important of which are: The designs of the decorative composition emerged bearing essential qualities and also expressive of an art that indicates originality and contemporary at the same time within a design fabric that carries a specific intellectual direction, which is to show the aesthetics of the originality of furniture designs, but in a contemporary way. This was embodied through the employment of elements Formalism of decorative composition Line, shape, color, texture, size, area and measure, direction. Relying on the foundations of decorative composition balance, proportion and proportion, unity and diversity, repetition, compatibility, harmony, supremacy, which created designs characterized by balance and wonderful organization of design elements and their relationships with each other to achieve an aesthetic value for those designs.